Katharine Hepburn en reine de cœur : Mary of Scotland (John Ford, 1936) - Jules Sandeau (Revue LISA)
This article examines how Mary of Scotland (John Ford, 1936) reworks Katharine Hepburn’s persona by articulating film analysis with the analysis of the discourses that surrounded the film on its release, namely in terms of its reception by the film audiences of the time. We shall study how J. Ford’s biopic uses the historical figure of Mary Stuart to try and resolve the contradictions between Hepburn’s gender and class identity in a socio-historical context marked by a reaffirmed patriarchal order building on middle-class values.